AN ANALYSIS OF HOLOCAUST ACT IN THE NOVEL THE DIARY OF A YOUNG GIRL - Cindy Lumape; Tini Mogea; Sanerita Olii (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study is to discuss the forms of holocaust violence that occurred in the novel the diary of a young girl by Anne frank. This research uses a qualitative method of presenting in a descriptive form (Ratna, 2007: 46). Data is collected in the form of words or descriptions of phenomena and not numbers. In this study, the researcher examined the situation of the object of study. The data analyzed in this study used a mimetic approach. Mimetic shorthand aims to examine reality. And also, by using a mimetic approach based on the supporting theory of Johan Galtung to group these Actions. In a sense, the researcher will describe the forms of violence in the Holocaust Act from Anne frank's novel the violence that exists on material objects into two forms, Structural Discrimination and Personal Discrimination. The two studies contain important points to explain the events of the holocaust against the Jews during the massacre